PENGARUH LINGKUNGAN INSTITUSIONAL DAN TIPE AUDITOR TERHADAP OPINI AUDIT - Awalia Zahra, Karina; Chariri, Anis (Diponegoro Journal of Accounting, 2013)
This study aimed to examine the effect of the institutional environment and the type of auditor's audit opinion. Institutional environment can be divided into strong institutional environment (DKI Jakarta) and a weak institutional environment (Non DKI Jakarta). Type of auditor auditor divided into local and non-local auditors. Audit opinion can be divided into an unqualified audit opinion and non unqualified audit. The research method used is quantitative method that examined the relationship between variables through hypothesis testing using 84 samples in 28 companies during the three periods. The sampling method of SOEs using purposive sampling, wheares the sampling method of non-SOEs using random sampling methods. Hypothesis testing techniques performed using logistic regression analysis using SPSS.The results obtained indicate that the institutional environment negatively affect the audit opinion. Meanwhile, positive effect on the type of auditor's audit opinion. This is consistent with a previous study conducted by Chan et al. (2010) who found that local auditors more easily issued an unqualified opinion on the institutional environment is weak compared to the strong institutional environment, as well as local auditors more easily issued an unqualified opinion on the institutional environment is weak compared to the local auditor.